An Advection-Diffusion Model for Radioactive Substance Dispersion Released From the Fukushima-Daiichi Nuclear Power Plant - Rizza, Umberto; Buske, Daniela; Bodmann, Bardo; Vilhena, Marco Túllio (Ciência e Natura, 2011)
.